1996
DOI: 10.1007/bf00145301
|View full text |Cite
|
Sign up to set email alerts
|

Interregional foodborne salmonellosis outbreak due to powdered infant formula contaminated with lactose-fermenting Salmonella virchow

Abstract: Spain's Salmonella surveillance system backed by regionally-based epidemiologists around the country made it possible to detect and halt the spread of a foodborne salmonellosis outbreak due to powdered infant formula contaminated with a lactose-fermenting strain of Salmonella virchow. Forty-eight cases involving children, mostly under 7 months old, were detected in 14 out of Spain's 17 Regions. The outbreak started in January and ended in June 1994. All cases were microbiologically confirmed. The implicated st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
5

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 7 publications
0
22
0
5
Order By: Relevance
“…Nevertheless, this low-grade contamination was responsible for a large outbreak of 136 confirmed cases and probably more nonconfirmed cases. In previous outbreaks of Salmonella infections linked to powdered milk [11][12][13][14][15] or to other food products, 6,7,10,16,17 similar low concentrations of Salmonella were reported suggesting a low infectious dose. A review of 11 outbreaks of salmonellosis for which the infective doses could be calculated revealed that in 6 outbreaks, calculated ingested doses were less than 10 3 organisms.…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, this low-grade contamination was responsible for a large outbreak of 136 confirmed cases and probably more nonconfirmed cases. In previous outbreaks of Salmonella infections linked to powdered milk [11][12][13][14][15] or to other food products, 6,7,10,16,17 similar low concentrations of Salmonella were reported suggesting a low infectious dose. A review of 11 outbreaks of salmonellosis for which the infective doses could be calculated revealed that in 6 outbreaks, calculated ingested doses were less than 10 3 organisms.…”
Section: Discussionmentioning
confidence: 93%
“…22 Contamination of dry milk products with Salmonella has been previously recognized and linked to several outbreaks affecting hundreds of infants. [23][24][25] It was possible that the contamination occurred in only some products made by certain manufacturers. Unfortunately, the information regarding the brands or manufacturers of the powdered milk was not collected.…”
Section: Discussionmentioning
confidence: 96%
“…Powdered infant formula also has been associated with outbreaks of illness due to Citrobacter and multiple Salmonella serotypes (13,(34)(35)(36)(37)(38). The degree to which E. sakazakii is a marker for a range of neonatal infections possibly related to powdered infant formula remains to be defined.…”
Section: Discussionmentioning
confidence: 99%